Technical Analysis of Lightning Arrester Replacement to Improve Customer's Power Grid Reliability - Zen, Hafidz Nindhom; Ibrohim; Baihaqi, Mochamad Faris (Fakultas Teknik Universitas Negeri Surabaya, 2025)
The reliability of the power distribution network in the tropics is particularly vulnerable to thunderstorm disturbances, which can cause asset damage and service interruptions. Lightning arrester (LA) as a primary protection component experiences performance degradation over time due to environmental factors, which has the potential to cause protection failure to thermal runaway. This study aims to conduct a technical analysis of the urgency of replacing existing LA units through a quantitative evaluation of isolation prisoners and a comparison of technical specifications with modern LA. The research methodology refers to the standard testing of insulation resistance with high DC voltage (2.5 kV - 5 kV), where values below the critical threshold of 1 Giga Ohm (GΩ) are identified as indicators of insulation failure after corrective cleaning measures are ruled out. The researchers analyzed that the value below the standard indicated a significant risk of leakage current that could trigger catastrophic failure of the Metal Oxide Varistor (MOV) block. The results of this analysis are expected to provide a strong technical justification for predictive maintenance policies, in order to improve surge protection capabilities, reduce the rate of disturbances, and ultimately strengthen the reliability of the electrical system comprehensively.